1997
DOI: 10.1523/jneurosci.17-14-05536.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cells in Laminae III and IV of the Rat Spinal Cord that Possess the Neurokinin-1 Receptor and Have Dorsally Directed Dendrites Receive a Major Synaptic Input from Tachykinin-Containing Primary Afferents

Abstract: Many neurons with cell bodies in laminae III or IV of the spinal dorsal horn possess the neurokinin 1 receptor and have dorsal dendrites that arborize in the superficial dorsal horn. We have performed a confocal microscopic study to determine whether these cells receive inputs from substance P-containing primary afferents. All neurons of this type received contacts from substance P-immunoreactive axons, and in most cases the contacts onto dorsal dendrites were very numerous. A great majority (90-100%) of subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
137
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 34 publications
(49 reference statements)
13
137
0
Order By: Relevance
“…Therefore, these results using immunocytochemistry do not favor a direct synaptic association between SP-containing afferents and neurons expressing the NK-1r. A confocal microscopic study adds to the controversy by showing that NK-1r immunoreactive neurons with cell bodies in laminae III-IV received a substantially higher number of appositions from SP immunoreactive boutons than neurons that expressed choline acetyltransferase but that were not NK-1r immunoreactive (11). This latter observation, together with our own results showing a preferential innervation by SP of nociceptive neurons (12), has led us to believe that SP in the spinal cord might not act in a diffuse manner as had been suggested (8) but, rather, that it might activate the NK-1r at a short distance from its site of release.…”
mentioning
confidence: 99%
“…Therefore, these results using immunocytochemistry do not favor a direct synaptic association between SP-containing afferents and neurons expressing the NK-1r. A confocal microscopic study adds to the controversy by showing that NK-1r immunoreactive neurons with cell bodies in laminae III-IV received a substantially higher number of appositions from SP immunoreactive boutons than neurons that expressed choline acetyltransferase but that were not NK-1r immunoreactive (11). This latter observation, together with our own results showing a preferential innervation by SP of nociceptive neurons (12), has led us to believe that SP in the spinal cord might not act in a diffuse manner as had been suggested (8) but, rather, that it might activate the NK-1r at a short distance from its site of release.…”
mentioning
confidence: 99%
“…CGRP has been postulated as a useful marker for primary afferent terminals (37) due to its fast disappearance after rhizotomy and its absence from neuronal bodies or axon terminals of intrinsic dorsal horn neurons (37)(38)(39). CGRP-positive afferents are present in laminae I and II of the dorsal horn (22,26,36,37,40). Unilateral dorsal rhizotomy of nine consecutive segments of the cervico-thoracic spinal cord caused a significant, though incomplete loss of CGRP-immunoreactive fibers in the spinal cord ipsilateral to the rhizotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The small C fiber DRG cells have been classified on the basis of their function and phenotype (20) into two groups: peptidergic and non-peptidergic. The C fibers that express neuromodulatory peptides (e.g., substance P; SP, calcitonin gene related peptide, CGRP) project to lamina I and lamina II outer of the dorsal horn (21)(22)(23). Many of these peptidergic fibers also express the p75 neurotrophin receptor (24).…”
Section: Degeneración De Los Terminales Aferentes Primarios De Rata Lmentioning
confidence: 99%
“…This was confirmed in electron microscopic studies that also showed that there is a significant mismatch between the presence of SP terminals and the NK-1 receptor; the latter had a much more extensive distribution (34), suggestive of extrasynaptic transmission (35,36, but see 37). In fact, despite the presence of dense SP immunoreactivity in lamina II (the substantia gelatinosa), the only element that expresses the NK-1 receptor in this region corresponds to the dorsally directed dendrites of large NK-1 receptor-expressing neurons in lamina III (38,39).…”
Section: Internalization Of Nk-1 Receptormentioning
confidence: 98%